2014
DOI: 10.2337/db13-1600
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Hindbrain Neurons Is Mediated by Portal-Mesenteric Vein Glucosensors During Slow-Onset Hypoglycemia

Abstract: Hypoglycemic detection at the portal-mesenteric vein (PMV) appears mediated by spinal afferents and is critical for the counter-regulatory response (CRR) to slow-onset, but not rapid-onset, hypoglycemia. Since rapid-onset hypoglycemia induces Fos protein expression in discrete brain regions, we hypothesized that denervation of the PMV or lesioning spinal afferents would suppress Fos expression in the dorsal medulla during slow-onset hypoglycemia, revealing a central nervous system reliance on PMV glucosensors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…In fact, small infusions of intra-portal, but not intra-jugular, D-glucose produced robust dopamine release in dorsal striatum [29]. This is consistent with the notion that glucose, upon duodenal transport, activates metabolic sensors residing within the portal-mesenteric system [37, 38]. In flies, recent accounts identified novel sugar-sensing candidates residing in the Drosophila brain.…”
Section: Separate Dopaminergic Pathways Encode Gustatory and Nutritiosupporting
confidence: 65%
“…In fact, small infusions of intra-portal, but not intra-jugular, D-glucose produced robust dopamine release in dorsal striatum [29]. This is consistent with the notion that glucose, upon duodenal transport, activates metabolic sensors residing within the portal-mesenteric system [37, 38]. In flies, recent accounts identified novel sugar-sensing candidates residing in the Drosophila brain.…”
Section: Separate Dopaminergic Pathways Encode Gustatory and Nutritiosupporting
confidence: 65%
“…Of note, altered neural feedback from the hepatoportal region to the brain has been previously shown to alter counterregulatory hormone secretion in the setting of hypoglycemia, albeit under very different experimental conditions. Elegant studies by Donovan and colleagues (24)(25)(26)(27) showed that denervation of the mesenteric region in the rat can alter the counterregulatory responses to insulin-induced hypoglycemia. This effect was only observed, however, when the fall in plasma glucose was slow (i.e., ~0.5 mg/dl/min), whereas disruption of neural input was of no consequence when the fall of the plasma glucose level was rapid (~1.3 mg/dl/min).…”
Section: Discussionmentioning
confidence: 99%
“…However, when peripheral portal-mesenteric vein glucose sensors are eliminated, the counterregulatory response to slow onset hypoglycemia, i.e., Յ1 mg·dl Ϫ1 ·min Ϫ1 , is severely diminished (FIGURE 2) (97). Concomitant with the suppression in the CRR is a failure for hindbrain neuronal activation, as denoted by Fos expression under these conditions (10). Interestingly, lesioning catecholaminergic afferents projecting from the hindbrain to the hypothalamus results in a similar impaired response to slow-onset hypoglycemia (48).…”
Section: Integration Of Peripheral and Central Glucose Sensingmentioning
confidence: 98%
“…Of the sensory CVOs, only the area postrema (AP) and subfornical organ (SFO) have been shown to contain glucose-sensing neurons (39,63). Although little is known regarding the potential contribution of the SFO in hypoglycemic detection, neurons in the AP do demonstrate robust Fos expression in response to systemic hypoglycemia and 2-deoxyglucose (10,80,100). There has been some suggestion that neurons of the arcuate nucleus may also be exposed to higher glucose concentrations, given their proximity to the median eminence (60).…”
Section: Central Glucose-sensing Neuronsmentioning
confidence: 99%